2010
DOI: 10.1007/s00401-010-0706-x
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of the peripheral nervous system in synucleinopathies, tauopathies and other neurodegenerative proteinopathies of the brain

Abstract: Involvement of the peripheral nervous system (PNS) is relatively common in some neurodegenerative proteinopathies of the brain and may be pathogenetically and diagnostically important. In Parkinson's disease, neuronal alpha-synuclein aggregates are distributed throughout the nervous system, including the central nervous system (CNS), sympathetic ganglia, enteric nervous system, cardiac and pelvic plexuses, submandibular gland, adrenal medulla and skin. The pathological process may target the PNS and CNS at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
119
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(125 citation statements)
references
References 172 publications
4
119
0
2
Order By: Relevance
“…It is not restricted to specific dopaminergic brainstem nuclei, but involves multiple areas of the central, autonomic, and peripheral nervous system, the retina, sympathetic and parasympathetic ganglia and nerves, skin, salivary glands, and other organs (for rev. see [23,24]). The pathology of NM symptoms in PD has been reviewed recently [20,[25][26][27][28].…”
Section: Introductionmentioning
confidence: 94%
“…It is not restricted to specific dopaminergic brainstem nuclei, but involves multiple areas of the central, autonomic, and peripheral nervous system, the retina, sympathetic and parasympathetic ganglia and nerves, skin, salivary glands, and other organs (for rev. see [23,24]). The pathology of NM symptoms in PD has been reviewed recently [20,[25][26][27][28].…”
Section: Introductionmentioning
confidence: 94%
“…The rational for this prodrome is based on the staging system of Braak, which suggested that the pathological process may not start in the SNpc (Braak et al). Examination of SNCA deposition patterns shows that the deposition of SNCA is not restricted to the brain, with deposits found in the olfactory bulb, peripheral nervous system, enteric nervous system (ENS), cardiac, and pelvic plexuses, etc (Wakabayashi et al, 2010 (Parkkinen et al, 2008). The speed of progression through the early stages remains unclear.…”
Section: Aims Of This Phd Projectmentioning
confidence: 99%
“…αS pathology has also been found in the peripheral nervous system (PNS): for example, in the enteric and pelvic plexus (19,20). And it has been suggested that αS pathology might originate in the nerves of the PNS and spread to the CNS (14).…”
mentioning
confidence: 99%